2018
DOI: 10.18178/joig.6.2.117-121
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Graphical Password Authentication System 'PassPositions'

Abstract: Passwords are often used to secure computers and information Passwords must be secure and easy to use. Traditionally used passwords are text-based passwords that use letters and numbers. However, text-based passwords are long and uncomfortable for users to use and are easy to steal from others. Today, passwords are required to meet the needs of many modern societies. Graphical passwords, which are recognized as an alternative to text-based passwords, have the potential to be superior to text-based passwords in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Certain websites use dynamic codes through e-mails or phone messages to provide authentication. It is one of the most successful two-factor authentication schemes, but the identified problem is that it mainly relies on other devices [3,4]. Some of the earlier studies found that the users can better recall images than text passwords.…”
Section: Introductionmentioning
confidence: 99%
“…Certain websites use dynamic codes through e-mails or phone messages to provide authentication. It is one of the most successful two-factor authentication schemes, but the identified problem is that it mainly relies on other devices [3,4]. Some of the earlier studies found that the users can better recall images than text passwords.…”
Section: Introductionmentioning
confidence: 99%
“…Graphical password systems can be classified as either recognition-based or recall-based approach; the latter of which is further divided into cued recall-based and pure recall-based approach [2,7,18]. In the recognition-based approach, the user selects a set of images from the available images in the registration phase which are recognized and reselected in the same sequence in the login phase.…”
Section: Introductionmentioning
confidence: 99%